Meralgia Paraesthetica And Beaus Line In Fractured LEG - Sathyanarayana B.D (Wolters Kluwer Medknow Publications, 2000)
Meralgia Paraesthetica and Beaus line appeared in a patient of simple fracture of right leg bones at fourth week of convalescence.